Effects of Mixed Rice Husk and Corn Cob as Filler on some Properties of Flexible Polyether Foam (Global Journal of Science Frontier Research, 2017)
This work studied the effects of local fillers; rice husk and corn cob, on flexible polyether foam. These fillers were mixed in the ratio of 50:50. The foam samples were produced using polyol and other recipes for foam production in the appropriate formulations. Varying loads of the mixed fillers of particle size of 0.25mm, such as, 5%, 10%, 15%, 20% and 25% were incorporated into the foam. The physicomechanical tests carried out on the foam samples were; density, hardness, compression, tensile strength and elongation at break. The creaming time, rising time, ignition time, char formation, char temperature and char duration of flexible polyether foam were also observed. The results showed that all the filled foams have higher densities than the unfilled foams as increase in filler loads increased the density of the foam samples. The fillers also modified other properties more than the unfilled foam used as a standard. The results of the flame tests showed that with increase in filler loads, the flammability of the produced foam was observed to be reduced. Hence, mixed rice husk and corn cob can be used as flame retardant in foam production and to improve other properties of the foam like density, load bearing ability and durability. More so, these fillers are agricultural wastes, completely organic and eco friendly, thus, can be used to produce biodegradable polyurethane foams.
Keywords: rice husk; corn cob; flexible polyether foam; mechanical and flammability properties